SYSTEMATIC REVIEW OF REMINISCENCE THERAPY: GLOBAL TRENDS & INDIAN ADAPTIONS - J H, NAVEENA; ARORA, SMRITI; Sharma, VIKAS (International Journal of Psychosocial Rehabilitation, 2020)
It is a systematic review on Reminiscence Therapy (RT) among older adults suffering from dementia and Alzheimer’s diseases with choice – parameters globally used in clinical settings. RT is in infancy stage in Indian clinical setting and we are establishing in this work various acceptable choice – parameters in India.To study the current status of research of RT in India and abroad. The recent research studies highlighted that non-pharmacological approach in treatment of old adults is becoming crucial and very encouraging in terms of acceptance amongst patients. This paper finds the research gaps from the rigorous review of literature and highlights future scope of this field. In this paper we systematically reviewed 25 recent high quality research papers using key words search method. The findings are discussed and research gaps pertaining to RT are listed accordingly. The key research papers are extracted from Scholarly repositories such as; PubMed, CINHAL, Cochrane, Google scholar, Research Gate. The findings are critically dissected to form meaningful and relevant research gaps.This paper is a systematic review analysis based on multiple intervention based RT studies done between 2001 and 2020. The research papers on RT available today majorly reports about aged adults (>60years) diagnosed with Dementia and Alzheimer’s disease (AD). This is a formative paper which establishes 15 Research gaps, which needs to be studied in detail. New parameter: “Health status” is added and discussed as per new trend in RT dimensions. Research gaps areillustrated for conducting further study. However, it was noticed that major global studies lack adequate sample size for generalization. It is promising to note that improvement in patients occurred even with a short span of RT approach. We must do specific analysis of long term and short term RT on various patients of multicultural nature.